Evaluation of muscle strength and quality in North African patients with chronic hepatitis B: A pilot case control study. Issue 1 (31st December 2023) - Bergaoui, Jihene; Latiri, Imed; Chaouch, Houda; Ben Abdallah, Jihene; Mrad, Sawssen; Maatamri, Wided; Letaief, Amel; Ben Saad, Helmi
ABSTRACT: Early detection of alteration of muscle strength, quantity, and quality, and sarcopenia is useful in non-cirrhotic chronic hepatitis B (NC-CHB) patients. Studies, which explored the handgrip strength (HGS) are scarce with questionable results, and no previous case-control study explored the presence of sarcopenia. The aim of this study was to assess the muscle strength [i.e.; HGS absolute (HGSA ), HGSA /body mass index (BMI)], muscle quantity [i.e.; appendicular skeletal muscle (ASM), ASM/height 2, ASM/total body weight (TBW), ASM/BMI], and muscle quality [i.e.; HGSA /total muscle mass (TMM), HGSA /ASM] of NC-CHB patients. This was a case-control study. Cases ( n  = 26) were untreated NC-CHB patients, and controls ( n  = 28) were 'apparently' healthy participants. Muscle mass was estimated via the TMM (kg) and ASM (kg). Muscle strength was evaluated via the HGS data [i.e.; HGSA (kg), HGSA /BMI (m 2 )]. Six variants of HGSA were determined: highest values for the dominant and non-dominant hands, highest value between the two hands, averages of the three measurements for the two hands, and the average of the highest values of the two hands. Muscle quantity was expressed in three relative variants (ASM/height 2, ASM/TBW, and ASM/BMI). Muscle quality was evaluated via relative HGS data adjusted by muscle mass (i.e.; HGSA /TMM, HGSA /ASM). Probable and confirmed sarcopenia were retained in front of low muscle strength, and low muscle strength and muscle quantity or quality, respectively. There were no significant differences between controls and NC-CHB patients in values of muscle i) Strength whatever the HGS' mode of expression (e.g.; HGSA /BMI: 1.59 ± 0.54 vs. 1.53 ± 0.54 m 2, p  = 0.622, respectively), ii) Quantity (e.g.; ASM/BMI: 0.79 ± 0.24 vs. 0.77 ± 0.23 m 2, p  = 0.883), and iii) Quality (e.g.; HGSA /ASM: 2.00 ± 0.25 vs. 2.01 ± 0.41, p  = 0.952, respectively). One NC-CHB participant had a confirmed sarcopenia. To conclude, both controls and NC-CHB patients had similar HGS values. Only one NC-CHB patient had a confirmed sarcopenia.